The ancient Greeks - Lassieur, Allison; local (New York : Franklin Watts, 2004)
Describes various groups within ancient Greek society, including athletes, philosophers, priests and priestesses, poets and playwrights, artists and architects, warriors, and slaves and workers, and includes a time line, a biographical dictionary, and a glossary.
The people of the government -- Scientists of Greece -- Greek athletes and sport -- Philosophers and thinkers -- Priests, priestesses, and the Greek religion -- Poets and playwrights -- Artists and architects -- Warriors -- Slaves and workers --
Includes bibliographical references (p. 104) and index.
School Library Journal
Legacy of the ancient Greeks.
Follett Library Resources
Keywords: 5-8; sears; sears; sears; sears -- Greece -- Civilization -- To 146 B.C.; Juvenile literature. -- Greece -- Civilization; To 146 B.C. -- Greece